(3TQM OjhGf GdMeGSIs - (3CHh GdaJhM KGHJ Hf eMeO GdLQLGfjs; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3bGd GdCSJGP CHh GdaJhM bQCJ gPG GdcJGH HHZOGO SfI KeGf hSHYjf hKdGKeGFI Ydi GdTjN CHj CMeO YHO GdSdGe Hf GdMSjf GdHUQi hbGd bGd CfTOfG CHh JeGe MHjH Hf ChS HGH ai GdTLGYI s
(3BNQgG (B:s
(3dh cfJ ef eGRf de JSJHjM EHdi TQ GddbjWI ef Cgd Hf TjHGfG bGd CHh GdaJhM JcdaJ JUMjM gPG GdcJGH hTQM ZQjHI heYGfjg , HYO Whd GdYO Hg hGddg GdeSJYGf ced cJGH GdMeGSI s
(3GdfSNI HgG MhGTs
(3fSNI YJjbIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B170s
Keywords: (3GdCOHs